Uncovering Europe's best goalscorers from the 2009-2010 season - Oberstone, J. (Journal of Quantitative Analysis in Sports, 2011)
The search for great goalscorers in football has been traditionally tunnel-visioned. Prestigious individual football awards, such as the Golden Boot and the Ballon d`Or, are almost automatically given to the player with the highest goal count. Simple. There is nothing usually complicated about this selection process—except, this one-dimensional approach may be missing some less-than-obvious gems of goalscoring by not considering the overall contributions a player makes to his team`s offensive performance as indicated by more subtle measures. The contributions made during the 2009-2010 season by the 20 leading goal scorers from each of the six most prestigious football leagues in Europe—the English Premier League, Spanish La Liga, Italian Serie A, German Bundesliga, French Ligue 1, and the Dutch Eredivisie—are examined. Statistical methods are used to (1) adjust for the significant disparity in the goal scoring prevalence between these leagues that promote unbiased comparisons and (2) account for the shorter, 34 game season used by two of the leagues as compared to the more common 38 game season.